Mortality among persons receiving tuberculosis treatment in Itezhi-Tezhi District of Zambia: A retrospective cohort study. - Eutra Chaaba; Josphat Bwembya; Eness Nyambe; Ramya Kumar; Ibou Thior; Kaminsa Seraphine; Gershom Chongwe; Vimbai Makwambeni; Victoria Musonda; Pauline Kasese-Chanda; Alwyn Mwinga (Public Library of Science (PLoS), 2023)
Itezhi-Tezhi District in southern Zambia has been reporting tuberculosis (TB) mortality rates that are fourfold higher than the national average of six percent. We conducted a retrospective cohort study to establish the demographic and clinical characteristics associated with mortality among persons under treatment for TB in Itezhi-Tezhi District, as well as the likely causes and time to death. We reviewed medical records for persons with TB registered in 19 public health facilities in Itezhi-Tezhi District between January 2015 and December 2018. Of the 506 persons with TB registered in the study period, 426 were included in the analysis. Of these, 71 (16.7%) died before completing treatment. The overall mortality rate was 31.8 per 1,000 person-months of observation. Most of the deaths (53 [74.7%]) occurred in the first month of treatment (median: 16 days; interquartile range: 5-52 days). In a multivariate Cox regression model, type of TB was found to be an independent predictor of mortality while on TB treatment. The risk of dying was more than twice higher for persons with clinically diagnosed PTB compared to those with bacteriologically confirmed PTB (adjusted hazard ratio = 2.2, 95% CI: 1.4-3.6). In a sub-analysis of persons with clinically diagnosed PTB, persons with TB who were on a community-based DOT plan were more than twice more likely to die compared to those on facility-based DOT plan (adjusted hazard ratio = 2.21, 95% CI: 1.1-4.8). Common likely causes of death were pulmonary TB disease (66.0%), anemia (12.8%), cardiac failure (4.3%), pneumocystis jiroveci pneumonia (4.3%), and gastroenteritis (4.2%). These findings show that most deaths occurred during the first month of treatment. Clinical evaluation at initiation of anti-TB treatment and during follow-up care, especially in persons with clinically diagnosed PTB, should include screening and treatment of other conditions.